1983
DOI: 10.1172/jci111074
|View full text |Cite
|
Sign up to set email alerts
|

Impaired stimulation of 25-hydroxyvitamin D-24-hydroxylase in fibroblasts from a patient with vitamin D-dependent rickets, type II. A form of receptor-positive resistance to 1,25-dihydroxyvitamin D3.

Abstract: A B S T R A C T We describe studies of the molecular defect in 1,25-dihydroxyvitamin D3 [1,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
42
0
2

Year Published

1986
1986
2009
2009

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(45 citation statements)
references
References 39 publications
1
42
0
2
Order By: Relevance
“…The individual described by Zerwekh et al (18) presented with a complex phenotype that was postulated to be due to mutations in both the vitamin D 25-hydroxylase and the VDR. We sequenced the exons of the CYP2R1 and CYP27A1 genes from this individual and found no mutations in either gene; however, biochemical and molecular analyses confirmed the presence of mutations in the VDR gene (41,42).…”
Section: -40)mentioning
confidence: 85%
“…The individual described by Zerwekh et al (18) presented with a complex phenotype that was postulated to be due to mutations in both the vitamin D 25-hydroxylase and the VDR. We sequenced the exons of the CYP2R1 and CYP27A1 genes from this individual and found no mutations in either gene; however, biochemical and molecular analyses confirmed the presence of mutations in the VDR gene (41,42).…”
Section: -40)mentioning
confidence: 85%
“…Hereditary 1,25-dihydroxyvitamin D resistant rickets (HVDRR), also known as vitamin D-dependent rickets, type II, is an autosomal recessive disorder that has been shown to be caused by mutations in the VDR (1,2). The disease is characterized by early onset rickets, hypocalcemia, secondary hyperparathyroidism, elevated 1,25(OH) 2 D 3 levels, and resistance to 1,25(OH) 2 (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). In the receptor positive cases the VDR was shown to exhibit a decreased binding affinity for DNA.…”
Section: Introductionmentioning
confidence: 99%
“…A frequently associated and unexplained finding in HVDRR is total scalp and body alopecia (3), a feature said to be present in the more severely affected patients (4). Studies from a number of laboratories have revealed that the cause of the target organ resistance in HVDRR is a defect in the intracellular vitamin D receptor (VDR) (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16).…”
mentioning
confidence: 99%
“…It was soon demonstrated that defects in the VDR were the likely cause of the HVDRR syndrome (5) and that different families exhibited different defects (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)). An additional useful finding was the demonstration that 1,25(OH)2D3 could induce the enzyme 25-hydroxyvitamin D-24-hydroxylase (24-hydroxylase) in multiple target tissues by a receptor-mediated process (27).…”
mentioning
confidence: 99%
See 1 more Smart Citation